Interdisciplinary didactic sequence to Strengthen environmental education in High School students - Zambrano Zambrano, Erika Vanessa (2025)
The study aimed to evaluate the impact of an interdisciplinary didactic sequence on strengthening environmental education, particularly in the understanding of chemical processes related to climate change among high school students at Unidad Educativa Colón Arteaga García, located in the parish of Ricaurte, Chone canton, Manabí province, Ecuador. A quasi-experimental pretest–posttest design without a control group was adopted, following a mixed-methods approach, and applying structured questionnaires and Likert-type scales to an intentional sample of 60 Chemistry students during the 2024–2025 academic year. Data were processed using Python, employing statistical tests and graphical representations. The results revealed significant improvements in the comprehension of greenhouse gases, chemical reactions associated with climate change, and the identification of mitigation alternatives. Likewise, student perception showed a predominantly positive acceptance of the applied methodology, highlighting the value of practical, experimental, and multimedia activities. These findings confirm that interdisciplinarity strengthens environmental literacy, fosters meaningful learning, and contributes to the formation of critical and responsible citizens in the face of current socio-environmental challenges.